2019
DOI: 10.1186/s13031-019-0224-y
|View full text |Cite|
|
Sign up to set email alerts
|

Informal healthcare provision in Lebanon: an adaptive mechanism among displaced Syrian health professionals in a protracted crisis

Abstract: Background Syrian healthcare workers (HCWs) are among those who fled the Syrian conflict only to face further social and economic challenges in host countries. In Lebanon, this population group cannot formally practice, yet many are believed to be operating informally. These activities remain poorly documented and misunderstood by the academic, policy and humanitarian communities. This study aims to understand mechanisms of informal provision of services, the facilitators and barriers for such pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
1
23
1
Order By: Relevance
“…Healthcare becomes a luxury and individuals resort to prioritization of medical conditions for which to seek healthcare. As a result, refugees seek alternative sources of healthcare such as homeremedies, informal healthcare providers [66], and pharmacists [63], as evidenced previously by 35% of registered Syrian refugees in the Baalbek-Hermel governorate seeking primary care from pharmacies [10]. Refugees in the present study also reported increasingly acquiring their medications from Syria [63] and occasionally travelling to Syria for surgical procedures despite associated ramifications.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Healthcare becomes a luxury and individuals resort to prioritization of medical conditions for which to seek healthcare. As a result, refugees seek alternative sources of healthcare such as homeremedies, informal healthcare providers [66], and pharmacists [63], as evidenced previously by 35% of registered Syrian refugees in the Baalbek-Hermel governorate seeking primary care from pharmacies [10]. Refugees in the present study also reported increasingly acquiring their medications from Syria [63] and occasionally travelling to Syria for surgical procedures despite associated ramifications.…”
Section: Discussionmentioning
confidence: 54%
“…Providing employment, jobskills training and investment opportunities, along with cash assistance can help alleviate many barriers experienced by refugees in securing their livelihood and provide more sustainable long-term solutions. Finally, with respect to improving access to health care, temporary policies, similarly to those adopted in Turkey [76], allowing Syrian healthcare providers to practice their professions among their refugee communities can be examined as potential approaches to relieve the high burden on the strained health care system of host communities [66]. Moreover, Syrian healthcare workers have good rapport and reputation within their own communities, thus they may be able to alleviate the financial strains and fears of social discrimination experienced among refugees when interacting with health workers from the host community.…”
Section: Implications For Humanitarian Systems and Potential Recommenmentioning
confidence: 99%
“…13,27 Some SRs also visited informal SR HCWs, as has been described in other regions of Lebanon. 19,28 As described in Table 4, a notable finding of this study is that participants sometimes avoided care due to perceived discrimination by HCWs. Participants frequently cited poor treatment by HCWs because of their ethnicity, socioeconomic status, or receipt of subsidized services.…”
Section: Discussionmentioning
confidence: 74%
“…No Syrian health professionals were employed by the clinic due to regulatory restrictions in Jordan. Syrian refugees in Lebanon were found to feel more comfortable receiving care from health professional staff from their own culture who have also endured displacement rather than from local staff [50]. Its is unclear how employing Syrian health professionals would impact on uptake of MHPSS services in this context.…”
Section: Health Care Seeking and Uptake Of Msf Mental Health And Psycmentioning
confidence: 99%